Four-year clinical remission of type 1 diabetes mellitus in two patients treated with sitagliptin and vitamin D3. (21st December 2016) - Pinheiro, Marcelo Maia; Pinheiro, Felipe Moura Maia; Torres, Margareth Afonso
Summary: Type 1 diabetes mellitus (T1DM) is a chronic disease characterized by autoimmune destruction of pancreatic beta cells and inadequate insulin production. Remission criteria in T1DM take into account serum levels of C-peptide and glycosylated hemoglobin, as well as the dose of insulin administered to the patient. However, remission of T1DM lasting longer than 1 year is rare. We describe here the cases of two young women who presented with positive glutamic acid decarboxylase (GAD) antibody and classic clinical manifestations of T1DM. Both patients had a prior history of Hashimoto's thyroiditis. They were initially treated with a basal-bolus regimen of insulin (glargine and lispro/glulisine). Once their blood glucose levels were controlled, they were started on oral sitagliptin 100 mg and vitamin D3 5000 IU daily. After this therapy, both patients achieved clinical diabetes remission for 4 years, along with a decrease in anti-GAD antibody levels. These benefits were probably associated with immunological effects of these medications. Inhibition of dipeptidyl peptidase 4 (DPP-4) in animal models deregulates Th1 immune response, increases secretion of Th2 cytokines, activates CD4 + CD25 + FoxP3 + regulatory T-cells and prevents IL-17 production. Vitamin D3 also activates CD4 + CD25 + FoxP3 + regulatory T-cells, and these medications combined can improve the immune response in patients with new-onset T1DM and probably promote sustained clinical remission. Learning points: The use of sitagliptin and vitamin D3 in patients with new-onset type 1 diabetes mellitus (T1DM) may help decrease the daily insulin requirement by delaying beta cell loss and improving endogenous insulin production. The use of sitagliptin and vitamin D3 in new-onset T1DM could help regulate the imbalance between Th17 and Treg cells. Age 14 years or above, absence of ketoacidosis and positive C-peptide levels in patients with T1DM are good criteria to predict prolonged T1DM remission. The determination of anti-GAD antibodies and C-peptide levels could be helpful in the follow-up of patients in use of sitagliptin and vitamin D3, which could be associated with prolonged T1DM clinical remission.